Effect of employee demographic characteristics and selected Human Resource Management Practices turnover intentions: A case of commercial banks in Eldoret Town, Kenya - P. Murupus, Norbert; J. Kipkebut, Dr. Dinah (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2015)
Organizational investment in Human Resources is an inevitable measure in pursuit of achievement of organizational goals. Organizations therefore must utilize a considerable amount of finances, materials and time in employee acquisition, maintenance and development. Despite the banking industries investing heavily in the acquisition and maintenance of its human resources, employees still quit their jobs in search of other alternatives. The objective of the present study is to establish the effect of employee demographic characteristics and selected Human Resource Management practices onemployees intention to turnover in the Banking industry. The study population consisted of Managerial, Clerical and Direct Sales Staff from twenty five (25) commercial banks in Eldoret town, Kenya. The study sampled 387 employees from ten (10) commercial banks. Questionnaire method was used to collect data. The data obtained was processed using the Statistical Package for Social Sciences (SPSS). Both descriptive and inferential statistics were used in data analysis; that is, Frequencies, means, standard deviation and Percentages which were presented in tables and charts. Pearsons Correlation analysis and Regression analysis were used to test the study hypotheses. The results of the multiple regression analysis showed that pay practices, procedural justice, marital status, education, job tenure and job positionwere critical factors in determining employee turnover intentions. The study recommends that banks should implement high commitment human resource management practices so as to enhance the retention of its employees.